PERANAN JUS BUAH MENGKUDU (Morinda citrifolia) DALAM MEMPERTAHANKAN KUALITAS SUSU PASTEURISASI KAMBING “PERANAKAN ETAWA” SELAMA PENYIMPANAN - Yuniani, Devi Rizky; Anam, Choiroel; Khusniati, Tatik; Utami, Rohula (Jurnal Teknologi Hasil Pertanian, 2017)
Pasteurized milk stored at cool temperatures generally have a relatively short shelf life. Antibacterialactivity of noni juice in maintaining the quality of pasteurized goat's milk stored at cold temperatures wasinvestigated. Characteristics of pasteurized goat's milk examined were organoleptic performances, microbialgrowth (total plate count and psychotrophic bacteria), chemical characteristics (protein, pH and acid total) withthe addition of noni juice at variation concentrations) (0%, 5%, 7.5%, 10%, and 12.5%) and times of storage(0.5, 10, 15 and 20 storage days). The results showed that the concentration of noni juice addition of 0 % -7.5 %on the parameters of colour, flavour, taste and homogenity and still were acceptable by consumers. Theinhibitory effects of TPC amount of growth were shown in 12.5% (2.8x101-3.3x101cfu/ml), and this inhibitoryeffects weren’t significantly different between each other of concentrations) (α> 0.05). The low decrease ofprotein content was indicated at concentrations of 7.5 % and still with the value of under SNI up to 20 days ofstorage (from 3.48 to 3.19%). The lowest decrease of pH and the increase acid total titration were shown atconcentrations of 5% with the values of pH (6.40 to 6.17) and acid total (0.20 %-0.22%). Based on organoleptic,microbial and chemical characteristics, it can be concluded that the best concentration of noni juice than that theothers can be added to the pasteurized goat milk during storage was 5%.